Optional Protocol to the UN Convention Against Torture - Murray, Rachel (Rachel H.) (Oxford : Oxford University Press, 2011)
The Optional Protocol to the United Nations Convention Against Torture was adopted in 2002 and provides for the establishment of national preventive mechanisms to stop torture from happening. This work sets out the powers of these mechanisms, their role within the international framework against torture, and suggests best practices.
The origins and background of OPCAT -- Drafting OPCAT : towards deadlock : 1991-2000 -- The text of OPCAT -- The scope of OPCAT -- The role of the Subcommittee on Prevention on Torture (SPT) -- The role of NPMs -- OPCAT within the broader UN and regional systems -- Regional trends toward ratification and implementation of OPCAT -- Conclusion: Emerging trends and the future of OPCAT.
Includes bibliographical references and index.
Keywords: United Nations. -- Committee against Torture; United Nations. -- Committee against Torture; Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment -- (1984 December 10). -- (2002 December 18); Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment; Torture (International law); Torture -- Prevention; Torture (International law); Torture -- Prevention